Inhibition of the Rumen Ciliate Entodinium caudatum by Antibiotics - Park, Tansol; Meulia, Tea; Firkins, Jeffrey L.; Yu, Zhongtang (Frontiers in Microbiology, 2017)
Axenic cultures of free-living aerobic ciliates, such as Tetrahymena thermophila and Paramecium aurelia, have been established and routinely used in laboratory research, greatly facilitating or enabling characterization of their metabolism, physiology, and ecology. Ruminal protozoa are anaerobic ciliates, and they play important roles in feed digestion and fermentation. Although repeatedly attempted, no laboratory-maintainable axenic culture of ruminal ciliates has been established. When axenic ciliate cultures are developed, antibiotics are required to eliminate the accompanying bacteria. Ruminal ciliates gradually lose viability upon antibiotic treatments, and the resultant axenic cultures can only last for short periods of time. The objective of this study was to evaluate eight antibiotics that have been evaluated in developing axenic cultures of ruminal ciliates, for their toxicity to Entodinium caudatum, which is the most predominant ruminal ciliate species. Scanning and transmission electron microscopy showed that the antibiotics damaged both the cell surface and nuclei of E. caudatum and increased accumulation of intracellular glycogen. Combinations of the three least toxic antibiotics failed to eliminate the bacteria that are present in the E. caudatum culture. The combination of ampicillin, carbenicillin, streptomycin, and oxytetracycline was able to eliminate all the bacteria, but the resultant axenic E. caudatum culture gradually lost viability. Adding the bacterial fraction (live) separated from an untreated E. caudatum culture reversed the viability decline and recovered the growth of the treated E. caudatum culture, whereas feeding nine strains of live bacteria isolated from E. caudatum cells, either individually or in combination, could not. Nutritional and metabolic dependence on its associated bacteria, accompanied with direct and indirect inhibition by antibiotics, makes it difficult to establish an axenic culture of E. caudatum. Monoxenic or polyxenic cultures of E. caudatum could be developed if the essential symbiotic partner(s) can be identified.